2012
DOI: 10.1016/j.cpr.2012.04.003
|View full text |Cite
|
Sign up to set email alerts
|

The combined cognitive bias hypothesis in depression

Abstract: Drawing from substantial evidence demonstrating cognitive biases in depression at various stages of information processing (i.e., attention, interpretation, memory, cognitive control), we argue for an approach that considers the interplay among these processes. This paper attempts to apply the combined cognitive bias hypothesis (Hirsch, Mathews, & Clark, 2006) to depression research and reviews competing theoretical frameworks that have guided research in this area. We draw on current findings from behavioral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
179
1
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 270 publications
(203 citation statements)
references
References 93 publications
(138 reference statements)
13
179
1
4
Order By: Relevance
“…Besides the paucity of studies and their methodological constraints (for a review, see Everaert et al, 2012), more importantly, we still lack a comprehensive insight into the (time)course of processing biases. That is, it remains untested how attention is deployed while emotional information is interpreted and how this sets the stage for emotional biases in memory.…”
Section: Limitations Of Prior Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the paucity of studies and their methodological constraints (for a review, see Everaert et al, 2012), more importantly, we still lack a comprehensive insight into the (time)course of processing biases. That is, it remains untested how attention is deployed while emotional information is interpreted and how this sets the stage for emotional biases in memory.…”
Section: Limitations Of Prior Researchmentioning
confidence: 99%
“…While this approach improves insight in how a specific bias affects behavior, it is also limited in that it does not show how these biased cognitive processes interact, which is a prerequisite for profound insight in each individual cognitive bias as well as emotionally distorted cognitive functioning as a whole. Acknowledging this limitation, a consensus is growing among theorists that cognitive biases should be studied in an integrative manner (e.g., Everaert, Koster, & Derakshan, 2012;Hertel & Brozovich, 2010;Hirsch, Clark, & Mathews, 2006). Interrelations among cognitive biases have been considered since the earliest theoretical frameworks of emotional processing in depression (e.g., Clark, Beck, & Alford, 1999;Ingram, 1984;Williams, Watts, MacLeod, & Mathews, 1988, 1997.…”
mentioning
confidence: 99%
“…In recent years, there is a growing consensus that cognitive biases should be studied in an integrative manner to augment understanding of each particular process as well as disordered cognitive functioning (see Everaert, Koster, & Derakshan, 2012;Hertel & Brozovich, 2010;Hirsch, Clark, & Mathews, 2006). It has been advocated that biased cognitive processes influence each other in that a bias at one stage (e.g., attention) affects the processing of this information at the other stages (e.g., interpretation).…”
Section: Indirect Effect Of Attention On Memory 3 Indirect Effects Ofmentioning
confidence: 99%
“…At the process level, considerable empirical research has shown that both subclinically and clinically depressed individuals selectively attend to negative information, tend to interpret ambiguous information in a negative manner, and recall disproportionately more negative memories (for reviews, see Gotlib & Joormann, 2010). Although there is extensive evidence supporting attention, interpretation, and memory biases in depression, the interplay between these cognitive mechanisms is not well understood.In recent years, there is a growing consensus that cognitive biases should be studied in an integrative manner to augment understanding of each particular process as well as disordered cognitive functioning (see Everaert, Koster, & Derakshan, 2012;Hertel & Brozovich, 2010;Hirsch, Clark, & Mathews, 2006). It has been advocated that biased cognitive processes influence each other in that a bias at one stage (e.g., attention) affects the processing of this information at the other stages (e.g., interpretation).…”
mentioning
confidence: 99%
“…Panel (b) represents increased REM sleep density, which would lead to a general enhancement in emotional memory according to the ATaC model. Panel (c) represents negatively-biased amygdala activity interacting with increased REM sleep density to cause a negative memory bias, which is believed to increase vulnerability to depression (Beck, 1967;Everaert, Koster, & Derakshan, 2012). N1, N2 and N3 -stages of non-REM (NREM) sleep.…”
Section: Figmentioning
confidence: 99%